Moderate intensity continuous training mitigates hypertension-induced renal fibrosis by inhibiting HIF-1α-mediated autophagy - Li, Yun; Yang, Xinyu; Chen, Zhuo; Dong, Wenyu; Chen, Xinhua; Wang, Wenhao; Li, Lingang; Ma, Wenjun; Chang, Qing (Frontiers in Physiology, 2025)
Introduction: Hypertension is a significant risk factor for kidney disease. Aerobic exercise has demonstrated positive effects in managing hypertensive nephropathy. However, the impact of exercise on hypertensive nephropathy remains contentious due to variations in exercise protocols. This study aimed to compare the effects of moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT) on renal fibrosis in spontaneously hypertensive rats (SHRs).Methods: SHRs underwent a 10-week treadmill training with moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT). The blood pressure in rats was measured following the conclusion of the final exercise training session. The renal function, levels of HIF-1α, fibrosis, and autophagy were evaluated by immunostaining and western blot in rat kidneys. The AKT/mTOR signaling pathway was also investigated. In vitro, we also treated angiotensin II-induced HK-2 cells with inhibited or overexpressed HIF-1α and tested the changes in fibrosis and autophagy by immunostaining and western blot. Following treatment with lysosomal inhibitors (chloroquine), the expression of fibrosis was further investigated.Results: Our findings indicated that MICT improved renal function and inhibited fibrosis through downregulation of HIF-1α and autophagy, whereas HIIT did not lead to significant improvement. Additionally, inhibition of HIF-1α attenuates Ang II-induced fibrosis and autophagy in HK-2 cells. HIF-1α overexpression had the opposite effect. CQ further alleviates fibrosis.Conclusion: These findings had elucidated the potential of MICT to ameliorate renal fibrosis caused by hypertension by targeting HIF-1α-regulated autophagy.